The Immunoproteasome Subunits LMP2, LMP7 and MECL-1 Are Crucial Along the Induction of Cerebral Toxoplasmosis - French, Timothy; Israel, Nicole; Düsedau, Henning Peter; Tersteegen, Anne; Steffen, Johannes; Cammann, Clemens; Topfstedt, Eylin; Dieterich, Daniela; Schüler, Thomas; Seifert, Ulrike; Dunay, Ildiko Rita (Frontiers in Immunology, 2021)
Cell survival and function critically relies on the fine-tuned balance of protein synthesis and degradation. In the steady state, the standard proteasome is sufficient to maintain this proteostasis, however, upon inflammation, the sharp increase in protein production requires additional mechanisms to limit protein-associated cellular stress. Under inflammatory conditions and the release of interferons, the immunoproteasome (IP) is induced to support protein processing and recycling. In antigen presenting cells constitutively expressing IPs, inflammation-related mechanisms contribute to the formation of MHC class I/II-peptide complexes, which are required for the induction of T cell responses. The control of Toxoplasma gondii infection relies on Interferon-γ (IFNγ)-related T cell responses. Whether and how the IP affects the course of anti-parasitic T cell responses along the infection as well as inflammation of the central nervous system is still unknown. To answer this question we used triple knockout (TKO) mice lacking the 3 catalytic subunits of the immunoproteasome (1i/LMP2, 2i/MECL-1 and 5i/LMP7). Here we show that the numbers of dendritic cells, monocytes and CD8+ T cells were reduced in Toxoplasma gondii-infected TKO mice. Furthermore, impaired IFNγ, TNF and iNOS production was accompanied by dysregulated chemokine expression and altered immune cell recruitment into the brain. Furthermore, T cell differentiation was altered, apoptosis rates of microglia and monocytes were elevated and STAT3 downstream signaling was diminished. Consequently, anti-parasitic immune responses were impaired in TKO mice leading to elevated levels of T. gondii burden and prolonged neuroinflammation in the chronic phase of infection. In summary we provide evidence for a critical role of the IP subunits 1i/LMP2, 2i/MECL-1 and 5i/LMP7 for the control cerebral Toxoplasma gondii infection and subsequent neuroinflammation.